(untitled) - Masita, Rosita (LATERNE, 2017)
While learning language, students doesn’t only need materials, but also execises. Exercises through worksheets that has function to know whether materials, which has been learned, have been understood . The teacher can also prove by worksheets whether learning goal has been reached . When student learn a particularly language, like german, they need to learn four skills. They are listening, speaking, reading and writing. When students exercise their reading skill, they need also worksheet so that they can practice their understanding about information from a sentence or text. There are a lot of sources in book”Berliner Platz 1 NEU” and the theme of the book is “Deutsch im Alltag” that is so useful for the students because they learn not only a theory of language but also german culture. But not all worksheet can be applied in a class because they must be suitable with curricular 2013. Curricular 2013 is a curricular that set education system in Indonesia. Therefore a question appears, are the worksheets suitable with curricular 2013?. The research goal is to describe analytical process worksheets for reading exercises from book ”Berliner Platz 1 NEU” with curricular 2013. The research use descriptive qualitative method. Its found 14 suitable worksheets of 27 worksheets for reading skill. Keywords: reading skill, exercises, Berliner Platz 1 NEU